In vivo and in vitro Characterization of a Partial Mu Opioid Receptor Agonist, NKTR-181, Supports Future Therapeutic Development - Lee, Alex S.; Tiwari, Suchi; Bishop, Isabel; Matossian, Vartan; Romaneschi, Nicole; Miyazaki, Takahiro; VanderVeen, Laurie; Zalevsky, Jonathan; DeFea, Kathryn; Cahill, Catherine M.; Walwyn, Wendy M. (Frontiers in Pain Research, 2021)
Mu opioid receptor agonists are well-known and frequently used clinical analgesics but are also rewarding so are highly addictive and are often abused. This may lead to opioid use disorder which effects millions of people worldwide. Novel compounds are urgently needed to treat this disorder. As opioids are effective analgesics and opioid use disorder often occurs in conjunction with chronic pain, these novel compounds may be opioids, but they must have a low abuse liability. This could be mediated by diminished or slowed blood-brain barrier transport, slowed target receptor binding kinetics and a long half-life. NKTR-181 is a PEGylated oxycodol and mu opioid receptor agonist that has slowed blood-brain barrier transport, a long half-life, and diminished likeability in clinical trials. In this study we examined the signaling and behavioral profile of NKTR-181 in comparison with oxycodone to determine whether further therapeutic development of this compound may be warranted. For this preclinical study, we used a number of in vitro and in vivo assays. The signaling profile of NKTR-181 was determined by electrophysiological assessment of mu opioid receptor-Ca2+ channel inhibition in the nociceptive neurons of rodent dorsal root ganglia. Heterologous cell-based assays were used to assess biased agonism and receptor trafficking. Different rodent behavioral models were used to define the NKTR-181 induced relief of affective and reflexive nociception and drug-seeking behavior as assessed by intravenous self-administration of NKTR-181. We found that NKTR-181 and oxycodone are partial agonists in G-protein signaling and Ca2+ channel inhibition assays and promote limited mu opioid receptor desensitization. However, NKTR-181 inhibits Ca2+ channels by a different mechanism than oxycodone and induces a different pattern of arrestin recruitment. In addition, NKTR-181 has a slower receptor on-rate and a slower rate of Ca2+ channel coupling than oxycodone. This signaling profile is coupled with a slower onset of antinociception and limited drug-seeking behavior when compared with oxycodone. Together with its known long half-life and slow blood-brain barrier transport, these data suggest that NKTR-181 could be further studied as a pharmacotherapeutic treatment modality for opioid use disorder.